2018
DOI: 10.1182/blood-2017-11-818617
|View full text |Cite
|
Sign up to set email alerts
|

RhoA G17V is sufficient to induce autoimmunity and promotes T-cell lymphomagenesis in mice

Abstract: Patients with angioimmunoblastic T-cell lymphoma (AITL) and other peripheral T-cell lymphomas that harbor features of follicular helper T (T) cells have a very poor prognosis. These lymphomas commonly present with paraneoplastic autoimmunity and lymphopenia. RhoA G17V mutation is present in 60% of T-like lymphomas, but its role in tumorigenesis is poorly understood. We generated transgenic mice that express RhoA G17V under the control of murine CD4 regulatory elements at levels comparable to a heterozygous mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 60 publications
2
99
1
Order By: Relevance
“…The interaction between TET2 and RHOA has been investigated in mouse models. Mice bearing a RHOA (p.Gly17Val) transgene under the control of T‐cell promoters showed an expanded Tfh population (Ng et al , ) similar to others who describe increased Tfh differentiation in animals with mutated RHOA (Cortés et al , ). The interaction between TET2 deficiency and RHOA (p.Gly17Val) has also been investigated in mouse models.…”
Section: Genetic Aberrations In Aitl and Ptcl‐nossupporting
confidence: 67%
See 1 more Smart Citation
“…The interaction between TET2 and RHOA has been investigated in mouse models. Mice bearing a RHOA (p.Gly17Val) transgene under the control of T‐cell promoters showed an expanded Tfh population (Ng et al , ) similar to others who describe increased Tfh differentiation in animals with mutated RHOA (Cortés et al , ). The interaction between TET2 deficiency and RHOA (p.Gly17Val) has also been investigated in mouse models.…”
Section: Genetic Aberrations In Aitl and Ptcl‐nossupporting
confidence: 67%
“…Animals bearing both gene defects showed expansion of CD4 + T cells in one study (Zang et al , ) while another demonstrated the development of T‐cell lymphomas with a long latency (Cortés et al , ). In a third such model, mice with defects in both Tet2 and Rhoa developed myeloid tumours before seven months but tended to produce T‐cell lymphomas after this time (Ng et al , ). One possibility, therefore, supported by the experimental evidence provided by mouse studies is that RHOA (p.Gly17Val) co‐operates with TET2.…”
Section: Genetic Aberrations In Aitl and Ptcl‐nosmentioning
confidence: 99%
“…[30][31][32] Mouse models have shown that RHOA G17V induces TFH specification, autoimmunity, and promotes lymphomagenesis in the presence of TET2 inactivation, indicating the synergistic effect of both mutations. [33][34][35] Cases of AITL with the RHOA G17V mutation have classical clinicopathological features and tend to have higher microvessel density, more FDC proliferation and a more pronounced TFH immunophenotype compared to wild-type cases, but no prognostic significance has been observed. 36,37 Various IDH2 point mutations at the R172 residue are present in about one-third of AITL cases.…”
Section: Pathological Features Of Nodal-based Ptclsmentioning
confidence: 99%
“…Loss of TET2 in hematopoietic progenitor cells is shown to predispose mice to both lymphoid and myeloid malignancies, but an additional RhoA G17V mutation in T cells is essential to initiate Tfh-driven lymphomas. [51][52][53][54] These studies also showed that combining TET2deficiency with the RhoA G17V mutation synergistically elevates Tfh differentiation, as well as PI3K-mTORC1 and TCR signaling pathways, which leads to AITL-like disease. Although spleen and swollen lymph nodes (,2 mm in diameter) in these mouse models share histological features with human AITL, they do not phenocopy the hypergammaglobulinemia and palpable lymphadenopathy seen in humans.…”
Section: Discussionmentioning
confidence: 84%